Simulated annealing optimization on multi-chamber mufflers hybridized with perforated plug-inlet under space constraints - CHIU, Mi Chie (Archives of Acoustics, 2009)
optimizing the acoustical performance of mufflers within a compact volume is necessary. To depress the acoustical performance, a multi-chamber muffler hybridized with perforated plug-inlet tubes which may dramatically increase the acoustical performance, is then adopted and optimized under space constraint. In this paper, both the numerical decoupling technique and simulated annealing (SA) algorithm for solving the coupled acoustical problem of perforated plug-inlet tubes and optimizing the muffler shape are used. To appreciate the acoustical ability of the new mufflers, traditional multi-chamber mufflers with extended inlet tubes have been assessed. Furthermore, noise reductions in broadband and pure tones noise are also introduced. But before the SA operation can be carried out, the accuracy of the mathematical model has to be checked by experimental data. Results reveal that the maximal STL is precisely located at the desired target tone. In addition, the acoustical performance of mufflers conjugated with perforated plug-inlet tubes is superior to that hybridized with extended inlet tubes. Moreover, the more chambers the mufflers have, the higher acoustical performance they will reach. Consequently, we demonstrate a successful SA application to the muffler design.